Not so much a high point as a watery low point: looking again at the relationship between dūn-names and medieval settlement - Lloyd, Abigail (Medieval Settlement Research, 2025)
The Old English element dūn, as it is frequently found in the earliest attested and surviving place-names, is often intrinsically linked with early medieval and medieval settlement. As others have pointed out, it is not just a topographic term referencing a hill form. This article is based on a national corpus of dūn-names assembled specifically for the purpose of investigating the nuanced meaning of this place-name element. A combination of interdisciplinary evidence, including linguistic, topographic, historic and archaeological analysis, is used to explore the corpus. A sense of enclosure, usually by virtue of topographic position, enhanced in places by archaeological enclosing works, appears to have motivated the coining of some of these early dūn-names. The role of a dūn emerges from this study; giving slight but sufficient elevation to enable early settlement and, in particular, the growing of crops in less waterlogged ground.